Statistical analysis of road crashes at the district level for the greater metropolitan area - Vargas Aguilar, Darío Ovidio (2025)
Due to the constant increase in the number of road crashes that occur in the country, it was sought to determine the socio-economic characteristics of the population and the variables of land use related to the frequency of road crashes at the district level in the Greater Metropolitan Area (GAM). This will make possible to include road safety criteria in urban planning policies. Statistical models of crash estimation were developed, using the negative binomial distribution based on the land use of the GAM. The socio-economic variables of the population and variables associated with the road network were included. The representative variables in each of the types of crashes analyzed were determined, such as the total population, and the estimation of expected crashes was performed for each of the districts under study. Additionally, the districts with the highest frequency were determined, where the Alajuela district stands out, which proved to be the most problematic. The districts of Heredia, Uruca, Hospital, San Nicolás, Río Segundo, among others, also resulted in significant excesses of crashes.